A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae) - Bello’, Cesare; Colonnelli, Enzo; Forbicioni, Leonardo; Osella, Giuseppe; Ruzzier, Enrico (Zootaxa, 2021)
A new genus of Entiminae, an endogean weevil of the tribe Otiorhynchini, Giavarhynchus Bellò, Osella & Ruzzier, gen. n., and its type species Giavarhynchus amicorum Bellò, Osella & Ruzzier, sp. n. are described. The new taxon is readily distinguished from all other members of the tribe due to the unique combination of lack of eyes, elongate rostrum with a ventral transverse furrow and excised lateral margins located at apical third, punctation of pronotum of two distinct sizes arranged in a distinctive pattern, interval 7 of elytra protruding from base of pronotum and crenulate basally, metafemora bearing a spine-like tooth much larger than that of pro- and mesofemora, female tibiae granulate on inner margin, bisinuous mesotibiae. The following synonymy is proposed: Nematocerus Reiche, 1849 (= Cyrtozemia Pascoe, 1872, syn. n.; = Holcorhinosoma Voss, 1939, syn. n.). New combinations are: Nematocerus cognatus (Marshall, 1916), comb. n.; Nematocerus dispar (Pascoe, 1872), comb. n.; Nematocerus pilipes (Morimoto, 2015), comb. n., all from Cyrtozemia; Nematocerus subtuberculatus (Voss, 1939), comb. n. from Holcorhinosoma. New tribal placement is: Pseudocratopus Hustache, 1921 from Otiorhynchini to Peritelini. New subgeneric placement is that of Otiorhynchus deceptorius Białooki, Germann & Pelletier, 2017 and of Otiorhynchus incisirostris Białooki, Germann & Pelletier, 2017 from Otiorhynchus (Lixorrhynchus) Reitter, 1914 to Otiorhynchus (Aranihus) Reitter, 1912.